Quality of Financial Sector Regulation and Supervision Around the World - Cihak, Martin (IMF Working Papers; Working Paper, 2008)
The paper analyzes the quality of financial sector regulation and supervision around the globe. Unlike studies that collect and analyze data on regulation and supervision "on the books," this study also analyzes available information on supervisory implementation, making use of data from IMF-World Bank assessments of compliance with international standards and codes. Incorporating supervisory implementation into the study provides an improved means of assessing countries' regulatory systems. We find that countries' regulatory frameworks score on average one notch below full compliance with the standards (on a 4-notch scale). There are substantial differences in the quality of regulatory and supervisory frameworks across countries, with the income level being a major factor.